KETERAMPILAN MANAJERIAL KEPALA SEKOLAH - Iskandar, Jamaluddin (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This paper aims to reveal the technical principal's managerial skills and factors that support and inhibit. It focuses on two main issues, namely: (1) What is the principal's managerial skills in terms of: Conceptual skills, Administrative skills, Human relationship skills, and. The concept of the principal leads to the Vision of the School Mission, and implements the open managerial concept in its management. The principal always cooperates, coordinated with all related elements and always gives motivation to the teachers and learners. Monitoring, evaluating and evaluating and constantly controlling school equipment. Factors that support the principal's managerial skills are all stakeholders in the school including; teachers, students, administrators, and society.